Variación espacio-temporal del índice de área foliar en un bosque mixto del sur de Morelia Michoacán - Santiago Bedolla, Ana Isabel (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The Leaf Area Idex (LAI) defined as half of the total leaf area (m2) per unit of soil surface area (m2), is one of the most important characteristics of the structure of the canopy of the plants. In addition, it is one of the most studied indices as a key variable in the ecosystem and the water balance. The processes that create spatial and temporal patterns of the LAI are still poorly understood, especially in humid regions. Therefore, the objective of this work is to evaluate the relationship between the main factors that control the spatio-temporal variation of the LAI and how it influences the distribution patterns of species in a mixed forest with different plant cover conditions. In the study site, a vegetal characterization was carried out and the presence of four coverings was found: Pine Forest (BP), Oak-Pine Forest (EP), Gallery Forest (BG) and Oak Forest (BE). The evaluation of the LAI was carried out using the method of hemispherical photographs, in addition soil moisture, phenology and micro environmental variables were evaluated. The results indicate for the BP the determining variables are environmental moisture and soil moisture in the first layer of the soil (0-5 cm). In the BE the environmental humidity, the humidity of the layer of 0-35 cm depth and the deficit of water vapor. While for the BG the determining variables are the environmental humidity, the deficit of water vapor, precipitation and the humidity of the superficial layer of the soil (0-5 cm). In the case of the EP, no correlation was found with the variables evaluated.

El índice de Área Foliar (IAF) definido como la mitad del área foliar total (m2) por unidad de superficie de suelo (m2), es una de las características más importantes de la estructura del dosel de las plantas. Además, es uno de los índices más estudiados como variable clave del ecosistema y el balance hídrico. Los procesos que crean patrones espaciales y temporales del IAF siguen siendo poco entendidos, especialmente en regiones húmedas. Por eso el objetivo de este trabajo es evaluar la relación entre los principales factores que controlan la variación espacio-temporal del IAF y cómo influye en los patrones de distribución de especies en un bosque mixto con diferentes condiciones de coberturas vegetales. En el sitio de estudio se realizó una caracterización vegetal y se encontró la presencia de cuatro coberturas: Bosque de Pino (BP), Bosque de Encino-Pino (EP), Bosque de Galería (BG) Y bosque de Encino (BE). La evaluación del IAF se realizó mediante el método de fotografías hemisféricas, además se evaluó la humedad edáfica, fenología y variables microambientales. Los resultados indican para el BP las variables determinantes son humedad ambiental y humedad edáfica en la primera capa del suelo (0-5 cm). En el BE la humedad ambiental, la humedad de la capa de 0-35 cm de profundidad y el déficit de vapor hídrico. Mientras que para el BG las variables determinantes son la humedad ambiental, el déficit de vapor hídrico, precipitación y la humedad de la capa superficial del suelo (0-5 cm). Para el caso del EP no se encontró ninguna correlación con las variables evaluadas.
Instituto de Investigaciones sobre los Recursos Naturales. Maestría en Ciencias en Ecología Integrativa
Keywords: info:eu-repo/classification/cti/2; INIRENA-M-2018-1226; Fotografía hemisférica; Dosel; Evapotranspiración; Humedad relativa; Fenología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1365